Bilinear Optimal Control for a Nonlinear Parabolic Equation Involving Nonlocal-in-Time Term - Gisèle Mophou; Arnaud Fournier; Célia Jean-Alexis (Axioms)
We study a bilinear optimal control problem for an evolution equation with a nonlinear term that depends on both the state and its time integral. First, we establish existence and uniqueness results for this evolution equation. Then, we derive weak maximum principle results to improve the regularity of the state equation. We proceed by formulating an optimal control problem aimed at steering the system’s state to a desired final state. Finally, we demonstrate that this optimal control problem admits a solution and derive the first- and second-order optimality conditions.